A smart skin PVC foil based on FBG sensors for monitoring strain and temperature - Silva, A. F. (2011)
Electronic products, including sensors, are often used in harsh environments. However, many parameters, such as severe weather conditions, high electronic noise, or dangerous chemical compounds in situ, may compromise the required high reliability. Therefore, development of a reliable sensing solution for monitoring those extreme conditions may become a very challenging task. This paper presents a smart skin foil developed to meet this specific need. Fiber Bragg grating sensors, one of the most reliable sensor solutions nowadays, were embedded in a thin foil made of polyvinyl chloride, giving rise to a smart structure with high durability and high resistance, and a dimensional stability above 99%. In addition, the fabrication processes used are based on a technology that allows the development of large sensing areas. The sensing foil shows a linear stretching profile, with a slope of 7.8 nm per 1% elongation. After submitting the developed structure to temperature cycles, it revealed a thermal behavior of 0.1 nm/°C. Since the smart sensing structure was fabricated using available industrial fabrication processes, it is a feasible and ready-to-market solution.